2015
DOI: 10.11613/bm.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation patterns in cancer: a clinical view

Abstract: Epigenetic mechanisms, such as DNA methylation, DNA hydroxymethylation, post-translational modifications (PTMs) of histone proteins affecting nucleosome remodelling, and regulation by small and large non-coding RNAs (ncRNAs) work in concert with cis and trans acting elements to drive appropriate gene expression. Advances in detection methods and development of dedicated platforms and methylation arrays resulted in an explosion of information on aberrantly methylated sequences linking deviations in epigenetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 100 publications
0
44
0
1
Order By: Relevance
“…There is growing evidence demonstrating that DNA methylation may deeply alter protein expression and potentially be a causative event in cancer (Fernandez et al 2012;Jones and Baylin 2002). Hypermethylation has been associated to the silencing of genes and to decreased gene expression of tumour suppressors, whilst hypomethylation can potentially result in genomic instability and reactivation of oncogenes (Litovkin et al 2014(Litovkin et al , 2015Paska and Hudler 2015;Weisenberger 2014). Based on genome-wide studies, abnormal methylation patterns have been detected in melanoma patients, highlighting potential markers for disease progression and also providing an important strategy for tumour diagnosis and treatment (Fu et al 2017;Guo et al 2018;Koga et al 2009).…”
Section: Linking Genes To Protein Expression and Functionmentioning
confidence: 99%
“…There is growing evidence demonstrating that DNA methylation may deeply alter protein expression and potentially be a causative event in cancer (Fernandez et al 2012;Jones and Baylin 2002). Hypermethylation has been associated to the silencing of genes and to decreased gene expression of tumour suppressors, whilst hypomethylation can potentially result in genomic instability and reactivation of oncogenes (Litovkin et al 2014(Litovkin et al , 2015Paska and Hudler 2015;Weisenberger 2014). Based on genome-wide studies, abnormal methylation patterns have been detected in melanoma patients, highlighting potential markers for disease progression and also providing an important strategy for tumour diagnosis and treatment (Fu et al 2017;Guo et al 2018;Koga et al 2009).…”
Section: Linking Genes To Protein Expression and Functionmentioning
confidence: 99%
“…DNA hypermethylation has been well characterized as a signature mode of regulation for cancer cell[171174]. DNA methylation typically involves methylation of cytosine within CpG-rich regions that are prominently present in promoter regions of tumor suppressor genes such as cyclin-dependent kinase inhibitor 2A (CDKN2A) and BRCA1[172, 175], and typically results in reduced expression of these genes.…”
Section: Epigenetic Silencing Of Duox In Cancermentioning
confidence: 99%
“…5-methyl-cytosine (m5Cyt) is the most investigated epigenetic modification, and alterations in genomic DNA methylation patterns have been confirmed to be associated with the development of pathological processes and diseases, including cancer (9,10). It has also been reported that DNA methylation patterns can be altered by medication, nutrients and chemicals (1113).…”
Section: Introductionmentioning
confidence: 99%